Sarcopenia and impairment in global cognitive, delayed memory, and olfactory function, among community-dwelling adults, in Jakarta, Indonesia: Active aging study - Yvonne Suzy Handajani; Elisabeth Schröder Butterfill; Antoninus Hengky; Sagita Pratiwi Sugiyono; Vincent Lamadong; Yuda Turana (Tzu Chi Medical Journal)
Objectives: This study aimed to investigate the association of sarcopenia among community-dwelling older adults with chronic conditions, lipid profiles, and cognitive ability measured by multiple assessment tools. Materials and Methods: This cross-sectional study involved 398 older adults aged 60 years and older who resided in Jakarta, Indonesia. The study participants were visited and interviewed by trained interviewers in the subdistrict office. Participants were clinically examined using a standardized protocol, which included the participants' medical history, general physical examination, cognitive assessment, and blood test for lipid profile. Sarcopenia was measured using three components that were muscle strength (measured by handgrip strength), physical performance (measured by 6-m walk speed), and appendicular skeletal mass (measured using bioelectrical impedance analysis). Association was tested using multivariate logistic regression and reported as an odds ratio. Results: Sarcopenia was significantly associated with older age (adjusted odd ratio [AOR]: 2.91, 95% confidence interval [CI]: 1.22–3.95) and smoking (AOR: 6.53, 95% CI: 2.89–14.73). Global cognitive impairment, word list recall impairment, and olfactory dysfunction have 191% (95% CI: 1.28–6.66), 141% (95% CI: 1.12–5.2), and 100% (95% CI: 1.11–3.61) increase of odds of having sarcopenia, respectively. Conclusion: Global cognitive impairment, word list recall impairment, and olfactory dysfunction could be the predictors of sarcopenia. Strategies and implementations directed more toward the improvement of cognitive impairment might improve or prevent sarcopenia. However, the exact causality between both variables still needs to be explored further.